A focus on the Chinese stingless bee honey (Hymenoptera, Apidae, Meliponini): Exploring physicochemical parameters for establishing quality standards - Zheng, Xing; Xu, Yandong; Huang, Yuan; Granato, Daniel; de Oliveira, Favízia Freitas; Vit, Patricia; Luo, Shiqi; Zhou, Xin; Guo, Jun; Dan, Zhen; Xue, Xiaofeng; Wu, Liming; et al. (Journal of food composition and analysis, 2025)
Stingless bee honey (SBH) is the most important product from stingless bee colonies with great economic value and health benefits. Nevertheless, there is little information on the physiochemical parameters of Chinese SBH, which also limits its utilization and quality control. In the period 2019–2023, we collected 89 Chinese SBH samples produced by five stingless bee species from four provinces in China. We performed comprehensive assessments of various SBH physicochemical indicators. These parameters include moisture, trehalulose, sucrose, fructose, glucose, total soluble solids, Baumé, ash, pH, electrical conductivity, 5-hydroxymethylfurfural, and free acidity. Our data revealed that the physicochemical parameters of Chinese SBH are consistent with earlier reported results from other countries. Notably, the Chinese SBH exhibited a relatively low level of 5-hydroxymethylfurfural (0–9.64 mg/kg), sucrose (0–0.43 g/100 g), and no diastase activity was detected. Chinese SBH was rich in trehalulose (4.26–37.65 g/100 g). After comparing these indexes with published data and with Australian/Malaysian samples, we proposed a new food standard for regulations of Chinese SBHs. These findings provide crucial insights into the Chinese SBH and contribute significantly to developing quality control and global standards for SBH. [Display omitted] •Physicochemical indicators of Chinese stingless bee honey (SBH) were measured.•Chinese SBH samples were collected from 4 provinces and 5 stingless bee species.•Chinese SBH showed low levels of 5-hydroxymethylfurfural and sucrose.•Chinese SBH was found to be rich in trehalulose.•A new food regulation standard for the Chinese SBHs was proposed.